Deja review. Microbiology and immunology - Chen, Eric M.; Chen, Joseph 1993- (New York McGraw-Hill, 2020)
"This high-yield, rapid-fire Q&A book simulates flashcards in a book to help medical students review microbiology and immunology for their course exams as well as prepare for the USMLE Step 1. It is also a great review for students in basic courses in other health-related programs"-- Provided by publisher.
I. Basic bacteriology : -- General principles (structure, genetics, growth) -- Classification and characteristics of medically important bacteria and normal flora -- Pathogenesis and host defense -- Laboratory diagnostics -- Antimicrobial drugs and vaccines -- II. Clinical bacteriology : -- Gram positive cocci -- Gram positive rods -- Gram negative cocci (Neisseria) -- Gram negative rods (Enterics) -- Gram negative rods (Respiratory) -- Gram negative rods (Zoonotic) -- Myobacteria (Tuberculosis, leprosy) --Actinomyces, nocardia, mycoplasma -- Spirochetes -- Chlamydia, rickettsia, & miscellaneous obligate intracellular organisms -- Minor bacterial pathogens (Ehrlichia/Anaplasma, Moraxella, haemophilus ducreyi) -- III. Basic virology : -- General principles (Structure, replication) -- Classifiation and characteristics of medically important viruses -- Pathogenesis and host defense (Interferons, nonspecific and specific immunity) -- Viral drugs and vaccines -- IV. Clinical virology : -- Herpesviruses -- Hepatitis viruses -- Paramyxovirus and orthomyxvirus -- Arboviruses (Toga, Flavi, Bunya) -- Retroviruses -- Remaining DNA viruses -- Remaining RNA viruses -- Prions -- V. Mycology : -- General principles of Mycology -- Cutaneous and subcutaneous mycoses --Systemic mycoses -- Opportunistic mycoses -- Antifungal mycoses -- Antifungal drugs -- VI. Parasitology : -- Protozoa -- Helminths -- VII. Immunology : -- Cells and signals of the immune system -- Major histocompatibility complex -- Innate immunity --Antibodies and complement -- Humoral immunity -- Cell-mediated immunity -- Hypersensitivity -- Tolerance and autoimmunity -- Immunodeficiency -- Laboratory use of antibodies -- VIII. Systems based microbiology : -- Cardiovascular system -- Respiratory system -- Gastrointestinal system -- Genitourinary system -- Ears, eyes, and nervous system -- Skin -- Musculoskeletal system.
Includes index.
Keywords: Microbiology -- Examinations, questions, etc; Immunology -- Examinations, questions, etc